Taxonomic variation in the supraorbital region of catarrhine primates. Issue 2 (24th November 2019) - White, Suzanna; Soligo, Christophe; Pope, Matt; Hillson, Simon
Abstract: Objectives: This study aimed to test the taxonomic utility of the catarrhine supraorbital region using 3D geometric morphometrics, with the aim of establishing its potential use in elucidating the position of more debated hominin groups. Materials and Methods: 230 3D coordinates were used to record the supraorbital morphology of two datasets: one containing 460 non‐hominin catarrhine primates from species and subspecies of Gorilla, Pan, Papio, and Macaca ; and the other containing 55 Pleistocene hominins from Homo, Australopithecus, and Paranthropus . Principal component analyses in tangent, form, and allometry‐free shape space were used to assess differentiation of taxa, with biological distinctiveness of taxa being established using step‐wise discriminant analysis with subsampling. Results: Results indicated that the recorded supraorbital morphology could be used to separate non‐hominin catarrhine primate genera, species, and subspecies, although accuracy was found to decrease with decreasing Linnaean rank. In addition, analyses in tangent space were found to produce the highest accuracy when classifying primates of known taxonomy. Biological distinctiveness of the middle and later Homo species was comparable to or higher than that of the non‐hominin primates, and relatively lower for the earlier groups of Homo . Discussion: This study indicates that the supraorbital region preserves taxonomic information that can be used to delineate between closely related groups, both within hominins and wider catarrhine primates. Therefore, this region may be used to provide insight when assessing the taxonomic affiliation of disputed hominin specimens.